Neural development and stem cells - Carpenter, Melissa; Vemuri, Mohan C.; Rao, Mahendra S. (Stem Cell Biology and Regenerative Medicine, 2012)
For the third edition of this work Dr. Rao and his fellow editors have worked diligently with the contributors to revise and expand each chapter.  Additional information about our understanding of the differentiation of pluripotent stem cells into the various neural cell types has been included. Particular attention has been focused on the chapters describing retinal epithelium and neuroglial differentiation, as these cells are currently being delivered in early phase clinical trials. Given the recent findings about the importance of cell death in tumorigenesis, the issue of cell death regulation in the nervous system has been further explored.  The issue of transdifferentiation has also been discussed and extensively updated given the recent findings on direct differentiation and reprogramming of cells.